Prescribing in the elderly. Issue 2 (February 2017) - Webber, Lucy
Prescribing in the elderly is a unique challenge faced by every GP. As the ageing population grows, more patients are presenting to GPs with an array of co-morbidities. The cumulative effect of this growth in morbidity is an increase in the prescribing of multiple medications. Although the use of appropriate medication can improve functional ability, slow disease progression and improve symptoms; medication can also cause adverse outcomes. Older patients are at particularly high risk of adverse outcomes, necessitating a rational and systematic approach to prescribing in the elderly. This article focuses on the challenges and pitfalls of prescribing in the elderly, and the ways in which GPs and the wider primary healthcare team can improve their practices for this group of patients.